INCREASE IN BIOETHANOL PRODUCTION BY ZYMOMONAS MOBILIS BY ADDITION OFZINC IONS IN THE ALCOHOL PRODUCTION MEDIA - PRERNA; SUTANU SAMANTA (International Journal of Pharma and Bio Sciences, 2013)
It has been reported in literature that Z. mobilis has two types of alcohol dehydrogenase gene (ADH), one is Zinc inducible, and another is Iron (Ferrous) inducible. Therefore, it was attempted to increase the alcohol production by inducing the alcohol dehydrogenase activity by addition of Zinc ions. It was standardized that 10 mM Zinc sulphate addition to alcohol producing broth resulted in maximum increase in alcohol production in both shake flask and 2 litre fermentor and it was 1.46 fold (49%) more than the control (using alcohol producing broth without Zinc sulphate). There was 3.2 fold increases in alcohol dehydrogenase activity when it was measured in presence of 10 mM Zinc sulphate as compared to control (ADH activity measured using same cell lysate in the absence of Zinc sulphate).